2023
DOI: 10.1038/s41598-023-29361-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel task of canine olfaction for use in adult and senior pet dogs

Abstract: While much work has been done in the field of canine olfaction, there has been little exploration of hyposmia or anosmia. This is partly due to difficulties in reducing confounds like training history and environmental distraction. The current study describes a novel olfaction test using spontaneous search behavior in dogs to find a hidden food treat in a three-choice task with both light-phase and dark-phase conditions. The study was performed in 18 adult control dogs, 18 senior/geriatric dogs enrolled in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…We found that young adult dogs (2-3 years old) performed the best, while younger and especially older dogs were less successful, which is in contrast to some previous findings showing no effect of age in olfactory tasks on smaller samples [33][34][35][36] . It should be noted that our age groups may not perfectly align with all breeds, but correspond with the general lifespan status of the dogs 50 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that young adult dogs (2-3 years old) performed the best, while younger and especially older dogs were less successful, which is in contrast to some previous findings showing no effect of age in olfactory tasks on smaller samples [33][34][35][36] . It should be noted that our age groups may not perfectly align with all breeds, but correspond with the general lifespan status of the dogs 50 .…”
Section: Discussioncontrasting
confidence: 99%
“…These changes likely decrease the olfactory ability of dogs. Based on the owners' perception, age-related decline in dogs' olfactory ability was reported 32 , although many studies have not found any age effect in olfactory tasks (companion dogs [33][34][35][36] ; working dogs 7,37 ), which might be explained by the different age range of the samples.…”
mentioning
confidence: 99%
“…Our research suggests that older dogs have difficulty using vision to navigate their environments when lighting is very limited. Because it is possible that olfaction ( 45 ) and hearing ( 46 ) are also impaired in older dogs, very low lighting conditions may be particularly difficult for older dogs to navigate in unfamiliar circumstances due to multisensory deficits limiting the ability of a dog to “switch” from one sense to another. Multisensory deficits contribute to an increase in abnormal behavior traits in dogs ( 47 ), namely increased tendency toward obsessive compulsive behaviors and reduced communication with owners.…”
Section: Discussionmentioning
confidence: 99%